Does thromboprophylaxis reduce symptomatic venous thromboembolism in patients with below knee cast treatment for foot and ankle trauma? A systematic review and meta-analysis. Issue 1 (February 2018) - Hickey, Ben A.; Watson, Ultan; Cleves, Andrew; Alikhan, Raza; Pugh, Neil; Nokes, Len; Perera, Anthony
Highlights: LMWH reduces the risk of symptomatic DVT in patients with cast treatment (NNT = 86). Major bleeding in these patients is rare (1 in 886, 0.11%). Mechanical thromboprophylaxis does not appear to reduce the incidence symptomatic VTE. Abstract: Background: Our aim was to determine the evidence for thromboprophylaxis for prevention of symptomatic venous thromboembolism (VTE) in adults with foot or ankle trauma treated with below knee cast or splint. Our secondary aim was to report major bleeding events. Methods: MEDLINE and EMBASE databases were searched for randomized controlled trials from inception to 1st June 2015. Results: Seven studies were included. All focused on low molecular weight heparin (LMWH). None found a statistically significant symptomatic DVT reduction individually. At meta-analysis LMWH was protective against symptomatic DVT (OR 0.29, 95% CI 0.09–0.95). Symptomatic pulmonary embolism affected 3/692 (0.43%). None were fatal. 86 patients required LMWH thromboprophylaxis to prevent one symptomatic DVT event. The overall incidence of major bleeding was 1 in 886 (0.11%). Conclusions: Low molecular weight heparin reduces the incidence of symptomatic VTE in adult patients with foot or ankle trauma treated with below knee cast or splint.